Realising the value of knowledge resources and capabilities: an empirical study. Issue 2 (11th March 2019) - Nguyen, Thi Nguyet Que; Ngo, Liem Viet; Northey, Gavin; Siaw, Christopher Agyapong
Abstract : Purpose: Drawing upon the resource-based view of the firm, this paper aims to develop and empirically validate a model that examines the relationships between technical knowledge management infrastructure (TKMI), social KM infrastructure (SKMI) and competitive advantage provided by KM (CAPKM). The authors argue that KM process capabilities account for the direct effects of TKMI and SKMI on CAPKM. Design/methodology/approach: The study used partial least squares —structural equating modelling (SEM) to empirically test the hypotheses using a sample of 251 firms from an emerging economy. The results were then confirmed using the bias-corrected bootstrap procedure. The study also conducted two robustness checks including examining a competing moderation model and performing fuzzy-set qualitative comparative analysis (fsQCA), a set–theoretic method that examines how causal conditions combine into all possible configurations of binary states to explain the desired outcome. Findings: The findings show that TKMI and SKMI have positive effects on CAPKM. In addition, KM process capabilities mediate the direct effects of TKMI and SKMI on CAPKM. Originality/value: This paper complements and advances previous research in several ways. Firstly, the paper develops a conceptual model that depicts the interrelationships between TKMI, SKMI, KM process capabilities and CAPKM. Secondly, this paper suggests the critical role of the "action" component (i.e. KM process capabilities) that capitalises on the KM resources in the creation of CAPKM.